Impact of out-of-pocket expenses on children with cancer in Tanzania: A mixed-methods economic study - Emily R. Smith; Pamela Espinoza; Happiness D. Kajoka; Henry E. Rice; Madeline Metcalf; Anna Tupetz; Cesia Cotache-Condor; Blandina T. Mmbaga; Catherine Staton; Esther Majaliwa (PLoS ONE, 2025)
Background For children with cancer in low- and middle-income countries, medical and non-medical expenses are often paid through out-of-pocket (OOP) expenditures, which pose significant barriers to timely care. Our study aims to estimate the impact of OOP expenditures for cancer care for children in Tanzania through a mixed-methods approach. Methods We used an explanatory mixed-method design to evaluate the impact of OOP expenditures for children receiving cancer care at the Kilimanjaro Christian Medical Center in Tanzania based on the Three Delays Framework. Quantitative data were collected to measure OOP expenditures and to assess the risk of catastrophic health expenditure or depth of impoverishment associated. Qualitative interviews were conducted to evaluate financial barriers and facilitators to care and were analyzed using thematic content analysis. Qualitative and quantitative data were triangulated to compare themes, identify areas of agreement or dissonance, and assess for complementarity. Results Thirteen caregivers of children with cancer at KCMC formed the study cohort. Most lived in a rural setting (92%) and were farmers or livestock keepers (68%). Quantitative analysis showed that total median OOP health expenditures were $53.01 (IQR: 26.50–106.01). All families were pushed further into poverty from the OOP expenses as shown by widening poverty gaps. Qualitative interviews revealed several themes related to financial challenges for families with cancer, particularly during the time period prior to definitive care including worry about job losses and having to sell assets to reach care. Data triangulation confirmed strong agreement between qualitative and quantitative data on the impact of financial barriers on care. However, families stated higher OOP costs in qualitative interviews compared to quantitative data. Conclusions Protecting families from impoverishment by reducing OOP costs during time periods prior to receiving definitive care may be a strategic way to improve timely diagnosis and early treatment for children with cancer.